The quality of colostrum and vitality of calves, born from cows with different reaction to stress experiences - O. M. Chernenko (Regulatory Mechanisms in Biosystems, 2017)
The article presents the results of studying cortisol concentration and creatine phosphokinase activity in the blood serum of 40 half-sib Ukrainian black and white dairy cows an hour after planned blood extraction, which was a stress experience. We divided the cows into three groups according to the distribution of cortisol concentration in the animals: I – high, II – average and III – low stress resistance. During the research, the cows from these groups were in their fourth month of lactation after their first calving. They were kept untethered in their summer quarters, natural pastures. The aim of the research was to identify the differences in the quality of colostrum, the vitality of the calves up to the age of 6 months, the vitality of the mother-cows, and also the influence of their different adaptation potentials in cases of abortion and stillborn calves among the cows from different groups. At the dairy complex where the research was conducted, the quality of the cows’ colostrum is not monitored. This is typical for most dairy plants of Ukraine. We found that the classes of A and M immunoglobulins did not depend upon which particular groups the animals belonged to, whereas the content of immunoglobulins of class G is 6.7 g/l higher, and the content of total protein is 8.9 g/l higher in the yield of colostrum of the cows from group 1. The influence of cows’ different levels of resistance to stress experiences on their incidence of abortions and stillborn calves was not determined. Gastroenteritis occurred among calves of cows from group 3 three times more often than with those of group 1. Vitality of calves from cows of groups 1 and 2 was significantly higher. Therefore, technological stress experiences of mother-cows have a negative effect upon the quality of colostrum and upon the vitality of calves. This factor ought to be taken into consideration in the exploitation of animals, especially during pregnancy in order to minimise stress and help individuals with less strong nervous systems. Solving the complex problems of increasing the vitality of calves involves in part guaranteeing their provision with colostrum immunity by compulsory control of the colostrum’ quality using a special aerometer (Colostrometer).